Segregation, housing and neighborhood dissimilarities: A case study for the city of Bochum - Said Benjamin Bonakdar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
The rising concentration of low-income households and ethnic minorities has become an important policy issue in Germany. The Ruhr Area is particularly interesting, because it is one of the largest conurbations in Europe and experienced radical structural changes in the past, which are connected to the boom and the deindustrialization of the coal mining and steel industry. Since there is no empirical evidence about the extent of residential segregation within the cities of the Ruhr Area, I use micro data on house-coordinates levels to investigate the urban structure of Bochum, which is located in the center of the conurbation. The results show that Bochum can be characterized by four different clusters under consideration of socioeconomic variables, dwelling rents and psychological indicators, e.g. captured by the so-called Sinus Milieus and Limbic Types. With a CHAID decision tree on dwelling rents I learned that especially dwelling size is a key separator between higher and lower dwelling prices in Bochum. The variables identified in the decision tree, like e.g. number of rooms or construction year, are used for hedonic price estimations within all clusters and show positive effects on dwelling rents. Finally, I found that, across all clusters, a rise in different satisfaction types also increase the odds of houses to be located in neighbourhoods with positive moving balance, which is a proxy for a high willingness-to-stay. – – Die zunehmende Konzentration von einkommensschwachen Haushalten und ethnischen Minderheiten ist zu einem wichtigen politischen Thema in Deutschland geworden. Das Ruhrgebiet ist hierbei besonders interessant, weil es einer der größten Ballungsräume Europas ist und in der Vergangenheit einen radikalen Strukturwandel erlebt hat. Dieser hängt mit dem Boom und der Deindustrialisierung des Kohlebergbaus und der Stahlindustrie zusammen. Da es bislang keine empirische Evidenz über das Ausmaß der residentiellen Segregation innerhalb der Städte des Ruhrgebietes gibt, verwende ich Mikrodaten auf Hauskoordinatenebene, um die Stadtstruktur von Bochum, das sich im Zentrum des Ballungsraums befindet, empirisch zu untersuchen. Die Ergebnisse zeigen, dass Bochum unter Berücksichtigung von sozioökonomischen Variablen, Wohnungsmieten und psychologischen Indikatoren, wie z.B. erfasst durch die sogenannten Sinus-Milieus und Limbic Types, durch vier verschiedene Cluster charakterisiert werden kann. Mit einem CHAID-Entscheidungsbaum Modell auf Wohnungsmieten konnte ich feststellen, dass insbesondere die Wohnungsgröße das zentrale Unterscheidungsmerkmal für hohe und niedrige Wohnungspreise in Bochum darstellt. Die im Entscheidungsbaum identifizierten Variablen, wie z.B. Anzahl der Räume oder Baujahr, werden für hedonische Preisschätzungen in allen Clustern verwendet und zeigen positive Effekte auf die Wohnungsmieten. Schließlich konnte ich für alle Cluster zeigen, dass ein Anstieg von verschiedenen Zufriedenheitsvariablen die Wahrscheinlichkeit erhöht, dass Häuser in Vierteln mit positiver Umzugsbilanz liegen, was als Proxy für eine hohe Willingness-to-Stay dient.
Keywords: R21; R23; R31; 330; Urban housing; housing prices; rent; neighbourhood characteristics; segregation